An Evaluation of the Psychometric Properties of the Attachment Behavior Checklist. (3rd July 2019) - Howard, Amanda R. Hiles; Dandy, Kristina; Martino, Maria; Howard, John D.; Cross, David R.
Abstract: The Attachment Behavior Checklist is a promising, but unvalidated, measure designed to assess attachment disturbances. Confirmatory and exploratory factor analyses were conducted. Results revealed a 5-factor solution best fit the data. Individual differences in the factors were examined. The Child Behavior Checklist was used to determine convergent and discriminant validity.